2022
DOI: 10.4103/ijo.ijo_2915_21
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of bacterial keratitis in North India: A retrospective analysis of six years at a tertiary care eye center

Abstract: Purpose: To analyze the pattern of bacterial pathogens causing infective keratitis and their resistance to the recommended antibiotics over six years. Methods: It was a retrospective study of 9,357 cases of bacterial keratitis from January 2015 to December 2020, at a tertiary care ophthalmic center. A total of 9,547 corneal specimens were obtained from the study subjects. Demographic details of the patients, pathogenic bacteria isolated, and their antimicrobial suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…We observed similar results to previous studies conducted in Alexandria and North India reporting that PA was the second most common bacteria isolated in MK and the most prevalent GN causative agent [ 33 , 34 ]. Nevertheless, a study conducted in Nottingham, UK, during 2015 to 2019, reported that PA was the most common isolated bacteria, followed by Staphylococci spp.…”
Section: Discussionsupporting
confidence: 91%
“…We observed similar results to previous studies conducted in Alexandria and North India reporting that PA was the second most common bacteria isolated in MK and the most prevalent GN causative agent [ 33 , 34 ]. Nevertheless, a study conducted in Nottingham, UK, during 2015 to 2019, reported that PA was the most common isolated bacteria, followed by Staphylococci spp.…”
Section: Discussionsupporting
confidence: 91%
“…Poorly controlled infection can result in progressive tissue destruction and severe visual impairment ( Durand et al., 2021 ). Common microorganisms responsible for bacterial keratitis include S. aureus , coagulase-negative staphylococci (CoNS), and S. pneumoniae ( Prokosch et al., 2012 ; Ahmed et al., 2022 ; Zhang et al., 2022 ). Corneal ulcers caused by bacterial infestation are often associated with persistent chronic ocular surface diseases, long-term corneal contact lens wear, eye trauma, and systemic or local corneal immunosuppression ( Amarasekera et al., 2019 ; Durrani et al., 2019 , 2020 ; Verner et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%